2022
DOI: 10.3390/met12101636
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Nucleation Potency of Substrates by Interfacial Segregation: An Overview

Abstract: During solidification of metallic materials, heterogeneous nucleation occurs on substrates, either endogenous or exogenous. The potency of the substrates for nucleation is mainly dependent upon the atomic arrangements on the substrate surface, which are affected by the lattice misfit between the substrate and the nucleated solid, the surface roughness at atomic scale, and the chemical interaction between the substrates and the melt. Extensive examinations on metal/substrate (M/S) interfaces at atomic scale by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Ma, et al observed Cu segregation at the Al/α-Al 2 O 3 interfaces [25]. Recently, segregation of the nd 1 elements, La or Y, at the Al/γ-Al 2 O 3 {1 1 1} interfaces has been realized experimentally and observed by TEM techniques [26]. Meanwhile, theoretical approaches, especially parameter-free AIMD methods, have been employed to investigate the atomic ordering at interfaces between liquid metal and oxide substrates [16,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Ma, et al observed Cu segregation at the Al/α-Al 2 O 3 interfaces [25]. Recently, segregation of the nd 1 elements, La or Y, at the Al/γ-Al 2 O 3 {1 1 1} interfaces has been realized experimentally and observed by TEM techniques [26]. Meanwhile, theoretical approaches, especially parameter-free AIMD methods, have been employed to investigate the atomic ordering at interfaces between liquid metal and oxide substrates [16,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Using ab initio molecular dynamics simulations, Wang et al [24] showed that heterogeneous nucleation plays an important role in the atomic arrangement of the substrate surface, which is influenced by the lattice misfit between the melt and solid, surface roughness, and the chemical interaction at the phase interface.…”
Section: Introductionmentioning
confidence: 99%